Fine scale genetic structure and extra-pair parentage in the socially monogamous Upland Sandpiper - Casey, Ashley E. (Kansas State University, 2008)
In birds, the offspring of females in socially monogamous species can be sired not only by their social partner (within-pair mating) but also by other males (extra-pair mating), resulting in broods of mixed paternity. Several hypotheses have been proposed which attempt to explain the adaptive significance of this behavior, including the genetic diversity hypothesis, the good genes hypothesis, the genetic compatibility hypothesis and the fertility insurance hypothesis. I report results of a 5 year population study of the Upland Sandpiper (Bartramia longicauda) at Konza Prairie Biological Station in northeast Kansas. My objective was to determine the genetic mating system of this socially monogamous shorebird, and determine which of the genetic hypotheses best explains the patterns of extra-pair paternity (EPP) in the population. As part of the analysis, I optimized laboratory protocols for genetic sexing of our monomorphic study species. Potential errors in molecular sexing have been previously described but usually result in females being misidentified as males. Here, I report evidence that events in PCR reactions can lead to the opposite error, with males misidentified as females. I recommend the use of multiple primer sets and large samples of known-sex birds for validation when designing protocols for molecular sex analysis. I genotyped birds and tested for the existence of EPP in 58 family groups of Upland Sandpipers. I found 15% of chicks and 30% of broods were the result of extra-pair paternity in this population, which is high in comparison to other socially monogamous shorebirds. Only 2% of chicks and 2% of broods were attended by females unrelated to the young. I tested ecological covariates known to influence EPP in other birds including relatedness of mated pairs, morphology of the within-pair male, and nest initiation date, as well as variables which signify genetic benefits, including morphology of the offspring and offspring heterozygosity, but found no significant relationships. None of the prevailing genetic hypotheses can fully explain the high rates of EPP in this population of Upland Sandpipers. However, the discovery of fine-scale genetic structure in female birds, but not in males, suggests female natal philopatry or male-biased dispersal. This sex-specific genetic structure could be a mechanism of inbreeding avoidance, thereby eliminating the need for females to choose mates based on relatedness. This study provides the first estimates of EPP for the socially monogamous Upland Sandpiper, and provides evidence that the inbreeding avoidance mechanism of engaging in extra-pair copulations does not seem to be as important in Upland Sandpipers as in other socially monogamous shorebirds. Future research should include the identification of extra-pair males and the determination of offspring fitness after departure from the nest.
Keywords: Bartramia longicauda; Extra-pair paternity; Breeding biology; Molecular sexing; Biology, Ecology (0329); Biology, Genetics (0369); Biology, Zoology (0472)